ANALISIS MODEL THRESHOLD GARCH DAN MODEL EXPONENTIAL GARCH PADA PERAMALAN IHSG - Susanti, Susanti; Zaenuri, Zaenuri; Mariani, Scolastika (Unnes Journal of Mathematics, 2016)
The purpose of this research were to know (1) the best model among TGARCH model and EGARCH model on predicting JCI value in BEI (2) the results forecasting JCI value in BEI using the best model for a few days later. This reseacrh focused on analysis of TGARCH and EGARCH models in forecasting JCI value. Procedure which used in this research were formulate problem, collecting data, analysis data dan conclusion. Data collected with documentation method that is collected secondary data and literature. Software EVIEWS 6 used as a analysis tool of JCI data. This research result in conclusions that is (1) The best model among models TGARCH and EGARCH models on predicting JCI value in BEI is TGARCH model (2) The results forecasting JCI value in BEI use TGARCH model for day 42th is 5112.81 and for day 43th until day 50th obtained 5112.82 (constant).